2019
DOI: 10.1177/0269215519827996
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between intra-articular Botulinum toxin type A, corticosteroid, and saline in knee osteoarthritis: a randomized controlled trial

Abstract: Objective: To compare the effectiveness of intra-articular injection (IAI) with Botulinum toxin type A (BTA), triamcinolone hexacetonide (TH), and saline in primary knee osteoarthritis. Design: A randomized controlled trial, with blinded patients and assessor. Setting: Outpatient rheumatology service. Subjects: Patients with knee osteoarthritis grades II and III. Interventions: Patients received IAI with 100 IU BTA, 40 mg TH, or isotonic saline solution (SS) 0.9%. Main measures: Patients were assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 28 publications
1
36
0
Order By: Relevance
“…It was also observable with different scores, as function or stiffness. Comparing TH to a saline injection, TH (40mg) had higher effectiveness than the placebo group in the four weeks in terms of pain in movement, pain scale, and ultra-sound measurement of synovial hypertrophy [70]. Treatment with 20mg or 40mg of TH produced equal relapse after six months in patients with chronic polyarthritis and when treating medium-sized joints.…”
Section: Plos Onementioning
confidence: 94%
“…It was also observable with different scores, as function or stiffness. Comparing TH to a saline injection, TH (40mg) had higher effectiveness than the placebo group in the four weeks in terms of pain in movement, pain scale, and ultra-sound measurement of synovial hypertrophy [70]. Treatment with 20mg or 40mg of TH produced equal relapse after six months in patients with chronic polyarthritis and when treating medium-sized joints.…”
Section: Plos Onementioning
confidence: 94%
“…The analysis found that BoNT-A IA injection had a greater improvement than placebo in terms of the VAS pain scale and WOMAC questionnaire score in both the short-term and long-term treatment periods. Additionally, in the studies of Bao et al 16 and Mendes et al, 17 BoNT-A IA injection demonstrated an acceptable safety profile, with improvements in the Physical Component Summary-36, Mental Component Summary-36, and ultrasound measurement of synovial hypertrophy.…”
Section: Discussionmentioning
confidence: 93%
“…The intention-totreat analysis was shown in one study. 17 All of the included studies were of high quality, with a Jadad scores rating A ( Table 2). The plot was highly symmetrical and no evidence of bias was found ( Figure 2).…”
Section: Quality Of the Individual Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some primary studies showed some encouraging results for botulinum toxins, there were controversial results by other studies (17). Studies have shown better improvement in pain and function scores in short term, but there is a lack of evidence for long-term efficacy of BTX (18). According to different methods of physiotherapy interventions in KOA, modalities like local heat, TENS and pulsed ultrasound besides exercise therapy are effective in pain reduction and function of KOA patients (19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%